PROSES PEMBUATAN PART DRAINASE PADA KAPAL TONGKANG MENGGUNAKAN MESIN CNC LASER CUTTING - Nugraha, Iqbal; Koswara , Engkos (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The drainage part of a barge is one of the important components that ensures the smooth operation of the ship in the waters. This part is designed to overcome the problem of water entering the ship, both due to rain and sea waves. The importance of this drainage part lies in the safety of the ship and the crew itself. This practical work report explains the process of making drainage parts on tonggkang ships using the CNC Laser Cutting O2 machine and the process of checking the quality of the drainage parts. The goal is to make drainage parts and ensure that they pass the Quality Control process. In the manufacture of this drainage part, there are several stages of manufacturing, namely the design process, the material selection process, the material measurement process, and then the process of making parts using a CNC Laser cutting machine. The manufacturing process is divided into two, namely the procedure of turning on the machine and the cutting process using a CNC Laser machine and then checking at Quality Control. In addition, this report discusses checking the quality of drainage parts. Through this practical work report, it is hoped that readers can gain insight into the process of making drainage parts on barges.